The Qur’an as the Foundation for Religious Moderation: An Analytical Study of K.H. Ahmad Muhamad Mustain Nasoha’s Perspective - Arif Prasetiyawan; Anysa Puspitasari; Dewi Audia Arumsari (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2026)
Purpose ̶ This study examines the thought of K.H. Ahmad Muhammad Mustain Nasoha on Qur’an-based religious moderation and its relevance to the Indonesian context. Design/methods/approach ̶ Using a qualitative library method, the analysis proceeded through four steps: selecting primary texts purposively, coding key concepts, organizing thematic categories, and interpreting them in dialogue with supporting literature. Findings ̶ The findings show that K.H. Mustain places the Qur’an as both normative and practical guidance through a hybrid interpretive model that balances textual fidelity with contextual application. This framework is applied in pesantren education, preaching, and interfaith engagement, and is connected to modern citizenship ethics. Conclusion ̶ The novelty of this study lies in demonstrating an “applied Qur’anic exegesis” that links moderation values with institutional and civic practices. Research Implication ̶ Practically, the study recommends curriculum integration, teacher training in contextual interpretation, and structured community dialogue programs to strengthen moderation in daily religious life.